+0  
 
0
133
2
avatar

help please

Guest Jun 1, 2017
Sort: 

2+0 Answers

 #1
avatar+90565 
+1

\(f(x)=\frac{3cotx}{2+e^x}\\ f(x)=\frac{3}{tanx(2+e^x)}\\ f(x)=3[(tanx)(2+e^x)]^{-1}\\ f'(x)=-3[(tanx)(2+e^x)]^{-2}\times [sec^2x(2+e^x)+e^xtanx]\\ f'(x)=\dfrac{-3[sec^2x(2+e^x)+e^xtanx]}{[(tanx)(2+e^x)]^{2}}\\ f'(x)=\dfrac{-3sec^2x(2+e^x)-3e^xtanx}{(tan^2x)(2+e^x)^{2}}\\\)

 

Any questions?

Melody  Jun 1, 2017
 #2
avatar
+1

Possible derivation:
d/dx((3 cot(x))/(2 + e^x))


Factor out constants:
 = 3 (d/dx((cot(x))/(2 + e^x)))


Use the quotient rule, d/dx(u/v) = (v ( du)/( dx) - u ( dv)/( dx))/v^2, where u = cot(x) and v = e^x + 2:
 = 3 ((2 + e^x) d/dx(cot(x)) - cot(x) d/dx(2 + e^x))/(2 + e^x)^2


Differentiate the sum term by term:
 = (3 ((2 + e^x) (d/dx(cot(x))) - d/dx(2) + d/dx(e^x) cot(x)))/(2 + e^x)^2


The derivative of 2 is zero:
 = (3 ((2 + e^x) (d/dx(cot(x))) - cot(x) (d/dx(e^x) + 0)))/(2 + e^x)^2


Simplify the expression:
 = (3 (-(cot(x) (d/dx(e^x))) + (2 + e^x) (d/dx(cot(x)))))/(2 + e^x)^2


The derivative of e^x is e^x:
 = (3 ((2 + e^x) (d/dx(cot(x))) - e^x cot(x)))/(2 + e^x)^2


The derivative of cot(x) is -csc^2(x):
Answer: | = (3 (-(e^x cot(x)) + (2 + e^x) -csc(x)^2))/(2 + e^x)^2

Guest Jun 1, 2017

4 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details